Biomedical engineering systems and technologies : 12th International Joint Conference, BIOSTEC 2019, Prague, Czech Republic, February 22-24, 2019, revised selected papers /: 12th International Joint Conference, BIOSTEC 2019, Prague, Czech Republic, February 22-24, 2019, revised selected papers. (2020) - Unknown
No abstract available